2017
DOI: 10.1038/s41598-017-04843-x
|View full text |Cite
|
Sign up to set email alerts
|

Age-related diagnostic value of D-dimer testing and the role of inflammation in patients with suspected deep vein thrombosis

Abstract: Previous reports have investigated the impact of age on D-Dimer testing in elderly individuals with suspected deep vein thrombosis (DVT), but data on the age-related diagnostic value of D-dimer in a sample covering a broad age range are limited. The present study determined age-specifically the diagnostic accuracy of D-dimer and compared it to C-reactive protein (CRP), a marker of inflammation, in 500 patients with suspected DVT from the VTEval project (NCT02156401). Sensitivity of D-dimer was lower in patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 39 publications
0
33
0
Order By: Relevance
“…A study validating the manufacturers’ recommended cut‐off values in populations < 50 years old would be of interest, and this has recently been addressed by Proschaska et al . .…”
Section: Discussionmentioning
confidence: 99%
“…A study validating the manufacturers’ recommended cut‐off values in populations < 50 years old would be of interest, and this has recently been addressed by Proschaska et al . .…”
Section: Discussionmentioning
confidence: 99%
“…Circulating D‐dimer is also elevated in patients with liver disease, coronary artery disease and other cardiovascular diseases, cancer, trauma, pregnancy, infections, inflammatory diseases, severe renal disease, recent surgical procedures, and advanced age as summarized in Table . However, the D‐dimer elevation in these conditions is less specific than for DVT/PE.…”
Section: Common Uses Of D‐dimer Assaysmentioning
confidence: 99%
“…Baseline levels of D-dimer varied in different age due to variability in the in ammatory and immune response dependent on age (29)and the elders were more likely to suffering from stroke, which could explain why the speci city of a standard D-dimer cut-off at 500ug/L for DVT prediction in elderly patients with stroke was comparatively low. A systemic review indicated that utility of an age-adjusted D-dimer cut-off (patient's age*10)ug/L) for elderly patients for ruling out DVT was recommended (30). The average levels of D-dimer when DVT detected were about 4-fold as the levels of that on admission in our study, which suggested that the gradually increased level of d-dimer was associated with DVT.…”
Section: Analysis Of the Changes In Laboratory Variables When Dvt Detmentioning
confidence: 53%